2017
DOI: 10.1016/j.amepre.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry-Assessed Latent Class Patterns of Physical Activity and Sedentary Behavior With Mortality

Abstract: Introduction Latent class analysis provides a method for understanding patterns of physical activity and sedentary behavior. This study explored the association of accelerometer-assessed patterns of physical activity/sedentary behavior with all-cause mortality. Methods The sample included 4,510 U.S. National Health and Nutrition Examination Survey participants aged ≥ 40 years enrolled in 2003–2006 with mortality follow-up through 2011. Participants wore a hip-worn accelerometer for 1 week that provided minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 37 publications
2
82
0
1
Order By: Relevance
“…van Nimwegen et al 37 reported that exercise training coupled with behavioral modification training increased total physical activity and daily energy expenditure in patients with Parkinson disease. Because sedentary behavior is an independent risk factor for all-cause mortality, 38 understanding how structured exercise affects nonexercise physical activity behaviors in patients with Parkinson disease will provide important clinical information on how to maximize the long-term therapeutic benefits of exercise in this population. This phase 2, multicenter futility design is of particular importance for the study of exercise in patients with Parkinson disease for several reasons.…”
Section: High-intensity Treadmill Exercise In Parkinson Diseasementioning
confidence: 99%
“…van Nimwegen et al 37 reported that exercise training coupled with behavioral modification training increased total physical activity and daily energy expenditure in patients with Parkinson disease. Because sedentary behavior is an independent risk factor for all-cause mortality, 38 understanding how structured exercise affects nonexercise physical activity behaviors in patients with Parkinson disease will provide important clinical information on how to maximize the long-term therapeutic benefits of exercise in this population. This phase 2, multicenter futility design is of particular importance for the study of exercise in patients with Parkinson disease for several reasons.…”
Section: High-intensity Treadmill Exercise In Parkinson Diseasementioning
confidence: 99%
“…Of these, 1010 articles were excluded after title and abstract screening and 23 full-text articles were assessed for potential eligibility. 10,11,[19][20][21][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Of these 23 articles, six studies met the criteria. 10,11,[19][20][21]33 From the remaining 17 studies contacted via email, five of them provided the requested results.…”
Section: Study Selectionmentioning
confidence: 99%
“…10,11,[19][20][21]33 From the remaining 17 studies contacted via email, five of them provided the requested results. [29][30][31][32]34 Eight studies did not provide cutoff point of LPA because data re-analysis was not available, [36][37][38][40][41][42]44,45 one study included participants with chronic kidney disease, 35 and the other three studies did not adjust for MVPA. 39,43,46 As a result, 11 articles were included in this review.…”
Section: Study Selectionmentioning
confidence: 99%
“…31 Our findings on the number of identified classes of accelerometer-based SB in an apparently healthy adult population using the growth mixture modeling approach are slightly different from previous studies. [12][13][14] In contrast to the NHANES studies that identified five to seven patterns of accelerometerbased SB, we decided to select the four-class model.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, study participants agreed to accelerometry monitoring for seven consecutive days, but it is still unclear whether this period is sufficient to accurately assess patterns of SB. 13 In addition, participants were informed that physical activity would be recorded over the measurement period. The administration of accelerometry may have introduced reactivity among the study participants.…”
Section: Discussionmentioning
confidence: 99%